2014
DOI: 10.1007/978-3-642-54792-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Information Flow in Boolean Programs

Abstract: Abstract. The quantitative information flow bounding problem asks, given a program P and threshold q, whether the information leaked by P is bounded by q. When the amount of information is measured using mutual information, the problem is known to be PSPACE-hard and decidable in EXPTIME. We show that the problem is in fact decidable in PSPACE, thus establishing the exact complexity of the quantitative information flow bounding problem. Thus, the complexity of bounding quantitative information flow in programs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Kaminski et al [35] studied the arithmetic complexity of almost sure termination for general probabilistic programs with unbounded data types. Chadha et al [13] showed PSPACE-completeness for the problem of bounding quantitative information flow for boolean programs with loops and probabilistic choice. A bound on pure differential privacy entails a bound on quantitative information flow, but not the other way around, and hence their result does not directly apply in our context.…”
Section: Related Workmentioning
confidence: 99%
“…Kaminski et al [35] studied the arithmetic complexity of almost sure termination for general probabilistic programs with unbounded data types. Chadha et al [13] showed PSPACE-completeness for the problem of bounding quantitative information flow for boolean programs with loops and probabilistic choice. A bound on pure differential privacy entails a bound on quantitative information flow, but not the other way around, and hence their result does not directly apply in our context.…”
Section: Related Workmentioning
confidence: 99%
“…However, when quantifying over all distributions the question is coNP-complete [35]. Checking whether the quantitative information flow of a program is less than a threshold has been shown to be PP-hard [34] (but in PSPACE) for loop-free boolean programs and to be PSPACE-complete for boolean programs with loops [10].…”
Section: Related Workmentioning
confidence: 99%